2017
DOI: 10.1002/elps.201700173
|View full text |Cite
|
Sign up to set email alerts
|

Pencil graphite electrodes for improved electrochemical detection of oleuropein by the combination of Natural Deep Eutectic Solvents and graphene oxide

Abstract: A novel methodology is presented for the enhanced electrochemical detection of oleuropein in complex plant matrices by Graphene Oxide Pencil Grahite Electrode (GOPGE) in combination with a buffer modified with a Natural Deep Eutectic Solvent, containing 10% (v/v) of Lactic acid, Glucose and H2O (LGH). The electrochemical behavior of oleuropein in the modified‐working buffer was examined using differential pulse voltammetry. The combination of both modifications, NADES modified buffer and nanomaterial modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In previous works, it has been demonstrated that NADES are enhancers for electrochemical detection of phenolic compound ,. This effect is due to the interaction of the analyte with the supramolecular structure of NADES, providing a suitable environment for electron transference.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous works, it has been demonstrated that NADES are enhancers for electrochemical detection of phenolic compound ,. This effect is due to the interaction of the analyte with the supramolecular structure of NADES, providing a suitable environment for electron transference.…”
Section: Resultsmentioning
confidence: 99%
“…This effect is due to the interaction of the analyte with the supramolecular structure of NADES, providing a suitable environment for electron transference. In order to challenge MW‐NADES, electrochemical measurements were performed at room temperature, following the conditions previously reported by Gomez et al . with some modifications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another liquid conductor that also offers great promise for soft electronics is deep eutectic solvents. [70][71][72][73][74] Since Abbott et al presented the first deep eutectic solvent example as a product of mixing choline chloride with urea, [75] it has aroused great Figure 7. a) A thermal diffusion model to explain the thermoelectric conversion.…”
Section: Deep Eutectic Solventsmentioning
confidence: 99%
“…Another liquid conductor that also offers great promise for soft electronics is deep eutectic solvents. [ 70–74 ] Since Abbott et al. presented the first deep eutectic solvent example as a product of mixing choline chloride with urea, [ 75 ] it has aroused great interests in green synthesis owing to their unique physicochemical properties like low volatility, electrochemical stability, and high ionic conductivity.…”
Section: Liquid Conductors For Soft Electronicsmentioning
confidence: 99%